Long-term benefits to Indigenous communities of extractive industry partnerships: Evaluating the Red Dog Mine. (June 2020) - Berman, Matthew; Loeffler, Robert; Schmidt, Jennifer I.
Abstract: Mining, and oil and gas companies developing resources on land historically occupied and used by Indigenous peoples have faced criticism for offering few benefits to local communities while inflicting environmental damage. The Red Dog Mine -- a joint venture between Teck Resources, Inc. and the NANA Regional Corporation -- has often been cited as an example for developing extractive industries in a way that does benefit Indigenous communities. The mine is located in an economically impoverished region in Northwest Alaska that has few other wage-earning opportunities for the largely Iñupiat population. Although the mine has brought demonstrable financial benefits to the region, questions persist about its long-term benefits to local communities. This paper assesses a suite of long-term benefits of the Red Dog mine, based on findings from unique 14-year panel dataset. The paper focuses on the direct effects of the mine on the individual Indigenous workers of the region. Specifically, the analysis addressed the following set of questions: How does employment at Red Dog affect workers' mobility and long-run earnings? How long do most local residents hired to work at the mine keep these jobs? What percentage of the mine workers live in the communities in the region, and what percentage of the total payroll do local workers receive? The findings illustrate the strengths and limitations of partnerships between Indigenous organizations and extractive industries, and offer insights relevant to Indigenous communities across the arctic and around the world as they plan development of local resources. Highlights: Most Indigenous mine workers were non-local: initially hired from outside the region. Locally hired mine workers earned much more than controls never working at the mine. Earnings of local mine workers remained higher than those of controls after 10 years. Local mine workers were somewhat more likely to leave the region than controls.